Mitochondrial proteins constructs and uses thereof - Lorberboum-Galski, Haya; Greif, Hagar (2019)
Disclosed are fusion protein constructs comprising a functional mitochondrial protein, that can enter mitochondria within intact cells. Further disclosed are methods of treating mitochondrial disorders by the disclosed fusion proteins and compositions therefor.